1995
DOI: 10.1111/j.1748-8583.1995.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Measurements: Who Is Using the Sums and For What Purpose?

Abstract: This article by David Preece and Michael Wood examines the deployment of quality measurements in organisational and inter‐organisational contexts. Four main issues are addressed: i) the arguments for measuring quality; ii) the managerial objectives which inform quality measurement utilisation; iii) the processes of introduction of quality measurements; and iv) the implications of all of the above for the orientation of the quality measurement (and quality management, where relevant) programme. the article draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Yet, there was also a greater emphasis on reporting systems which have the potential to monitor and control employees' contributions. Thus, the survey appears to confirm the literature which suggests that involvement will not necessarily result in empowerment (Sewell and Wilkinson, 1992) and that it may lead to the increased monitoring and control of employees' work (McArdle et al, 1995;Preece and Wood, 1995).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Yet, there was also a greater emphasis on reporting systems which have the potential to monitor and control employees' contributions. Thus, the survey appears to confirm the literature which suggests that involvement will not necessarily result in empowerment (Sewell and Wilkinson, 1992) and that it may lead to the increased monitoring and control of employees' work (McArdle et al, 1995;Preece and Wood, 1995).…”
Section: Discussionsupporting
confidence: 74%
“…Middle managers, whose role is pivotal to successful introduction (Hill, 1991), may be reluctant participants, with an attitude of compliance rather than commitment (Wilkinson and Witcher, 1991, p. 49) and, as already noted, the personnel department, which supposedly has responsibility for ensuring good employment practices, is often bypassed (Giles and Williams, 1991). There is also little evidence that attempts at involvement actually result in empowerment; in fact, the reverse may be the case, with the introduction of quality systems actually increasing the monitoring and control of employees' work (McArdle et al, 1995;Preece and Wood, 1995;Sewell and Wilkinson, 1992).…”
Section: Hr Practicesmentioning
confidence: 99%
“…The significance of IIP, therefore, lay in its utility as a marketing device; the``badge'' was important for retaining and attracting clients. There are connections here with Gouldner's (1954) classic study of a gypsum mine and factory, in which three types of bureaucratic``rules'' were identified:``mock'',``representative'' and`p unishment-centred'' (Preece and Wood (1995) make a similar link in their study of quality measurements). In the context of the case firms, IIP can be seen as an example of a``mock'' bureaucratic rule.…”
Section: Discussionmentioning
confidence: 72%
“…The study shows that external pressures can play a significant role in shaping the approach to quality. As other studies have demonstrated (Holliday, 1995;North et al, 1995;Preece and Wood, 1995) such pressures can lead to greater bureaucracy, labour intensification and closer control, while having little substantive impact on the sophistication of the product or service. However, the ATS experience illustrates that management can handle these pressures in ways that do not necessarily result in these negative consequences.…”
Section: Discussionmentioning
confidence: 94%
“…For the small firm practitioner wishing to move beyond the consultancy hype and the evangelism of many quality texts and manuals, the above points highlight the limitations of generic approaches to the implementation of quality. Even more searching questions are posed by the emerging critical treatments of the subject (Ghobadian and Gallear, 1996;Preece and Wood, 1995;Wilkinson and Wilmott, 1995). In particular, the contributors to the volume edited by Wilkinson and Wilmott, Making Quality Critical, set out to illuminate the social, political and economic forces that have shaped the emergence of quality as an issue for British management in the 1980s and 1990s.…”
Section: Learning From Othersmentioning
confidence: 99%